Path Analysis Study on the Direct and Indirect Effect of Factors Affecting Performance of Pharmaceutical Staff in Primary Health Centers in Bandung - Roseno, Mohammad; Widyastiwi, Widyastiwi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: Pharmaceutical staff plays an essential role in pharmaceutical services. Despite their role, several factors have been reported to cause suboptimal provision of pharmaceutical services.Objectives: This study aimed to examine the impact of physical environment, compensation, and motivation on organizational culture, and its implication on performance of pharmaceutical staff.Methods: The sample population comprised 149 pharmaceutical staff from 71 Primary Health Centers in Bandung, selected using total sampling. The inclusion criteria were pharmaceutical staffs in 71 Primary Health Centers in Bandung. Pharmacy personnel who refused to give consent or did not complete filling out instruments were excluded. Data were collected using a questionnaire to assess the participants’ perceptions of physical environment, compensation, motivation, organizational culture, and performance. Direct and indirect effect of each variable and its correlation was determined by path analysis. All analysis were performed by using the SPSS version 25. Results: The physical environment, compensation, motivation, and organizational culture contributes 66.4% to overall performance of pharmaceutical staffs. Physical environment and motivation significantly influenced performance (b=0.331 and b=0.245, respectively) directly and indirectly through organizational culture. Compensation had neither direct and indirect impact on performance. Organizational culture has a direct effect on pharmaceutical performances (b=0.789). Organizational culture is an intervening variable of the physical environment and motivation impact on performance.Conclusion: These findings suggest that the physical environment dan motivation directly influenced performance of pharmaceutical staffs, while financial compensation had no direct or indirect impact. Organizational culture significantly influences the performance by intervening the physical environment and motivation factors.